Indonesian Twitter User Sentiment towards PeduliLindungi App in Strengthening Smart Living during COVID-19 - Kurniawan, Rendy; Rachmawati, Rini (Center for Southeast Asian Social Studies (CESASS), 2023)
The COVID-19 pandemic has changed lifestyles in counties and cities in just a few months by putting technology at the forefront of fighting the pandemic. Handling COVID-19 can show technological disparities and inequalities between different cities, given the COVID-19 condition that continues to plague various towns and districts in Indonesia. One of the steps to handle it, namely providing national-scale public services with a COVID-19 tracker application called PeduliLindungi. Using the PeduliLindungi app in each city and Regency is a form of Smart City implementation in Indonesia, especially in the Smart Living dimension. PeduliLindungi is a must-have app for residents who move or enter public facilities to create a safe and healthy city during the COVID-19 pandemic. Given the WFH trend, Twitter has become an abundant data source to collect public opinion regarding PeduliLindungi applications needed to improve service quality. This study aims to analyze Twitter users’ sentiments towards the PeduliLindungi app usage in the context of strengthening smart living. Sentiment analysis was performed in this study using the VADER Sentiment towards tweets dataset collected over two different periods. The results show that the Indonesian government effectively uses Twitter to answer questions and share COVID-19 and PeduliLindungi-related information with the public. Negative sentiment was expressed more towards the PeduliLindungi app than positive sentiment due to public unrest over data security and constraints encountered in using the PeduliLindungi app.